Wakaf tunai dari perspektif generasi milenial - Haerunniza, Feiza Aulia; Muhammad, Rifqi (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This paper aims to discuss or review cash waqf from the perspective of millennial generation in Indonesia. Cash waqf is increasingly popular because it is flexible and has a relatively low value so it can attract more wakifs. This cash waqf provides greater benefits, for example cash is channeled into sharia investment instruments, such as state sukuk for road construction. This paper discusses the millennial generation who uses technology in all aspects of life. By using these devices, the millennial generation can become more productive and efficient individuals. The potential for the millennial generation from developing cash waqf in Indonesia is considered quite large, namely it is assumed that 20% of the young generation of Muslims are capable of waqf, so the potential cash profit reaches IDR 1.18 trillion.